1997
DOI: 10.1063/1.120072
|View full text |Cite
|
Sign up to set email alerts
|

Formation of carbon-induced germanium dots

Abstract: A very small amount of pre-deposited C on a Si substrate causes island formation after epitaxial growth of less than 2 monolayers Ge. These C-induced Ge dots can be as small as 10 nm in lateral size and 1 nm in height. Their areal density is 1011 cm−2. Intense photoluminescence signal from these small Ge quantum dots is observed reaching a maximum for 2.1±0.3 monolayers of Ge. In the initial stages of island formation, the optical transition of the wetting layer is blue-shifted by strain compensation effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
80
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(84 citation statements)
references
References 16 publications
4
80
0
Order By: Relevance
“…1͑a͔͒, similar to what was previously observed in the case of C predeposition directly on Si͑001͒. 13 By increasing the Ge composition of the buffer layer we observe a significant decrease of island density ͓see 1͑b͒-1͑d͔͒ with the consequent increase in average island size.…”
Section: Density Control On Self-assembling Of Ge Islands Using Carbosupporting
confidence: 74%
See 1 more Smart Citation
“…1͑a͔͒, similar to what was previously observed in the case of C predeposition directly on Si͑001͒. 13 By increasing the Ge composition of the buffer layer we observe a significant decrease of island density ͓see 1͑b͒-1͑d͔͒ with the consequent increase in average island size.…”
Section: Density Control On Self-assembling Of Ge Islands Using Carbosupporting
confidence: 74%
“…9 Other routes include Ge deposition on relaxed SiGe/ Si buffer layers 10,11 and deposition on buried dislocation networks. 12 Another relevant bottom up strategy towards efficient dot engineering involves surface modification through deposition of sub monolayer amounts of impurities 13 that can reduce the diffusion length ͑i.e., enhancing dot density͒ and alter the energetics of nucleation. This approach has recently gathered renewed interest, having as examples the cases of surfactant mediated growth in the presence of Sb ͑Ref.…”
Section: Density Control On Self-assembling Of Ge Islands Using Carbomentioning
confidence: 99%
“…Surprisingly, it turned out that carbon can be incorporated in concentrations up to a few percent which is many orders of magnitude above its thermodynamic solubility of carbon in silicon. Most recently carbon incorporation during crystal growth of silicon-germanium alloys was used to induce Si-Ge quantum dot structures [9].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Quantum confinement effect in these islands is useful for optoelectronic device applications based on the Si technology. [3][4][5][6][7][8][9][10][11][12][13][14][15] The homoepitaxial Si/Si growth is also important because isotopically controlled Si structures are expected to serve as building blocks of novel application devices, such as a quantum computer utilizing Si nuclear spin. 16 Himpsel and co-workers have experimentally demonstrated that vicinal Si͑111͒ surfaces can serve as templates for self-assembly of one-dimensional ͑1D͒ nanostructures, 17,18 because a regular array of straight steps can be obtained on these surfaces.…”
Section: Introductionmentioning
confidence: 99%